2019
DOI: 10.1038/s41598-019-43694-6
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of modern topical sealants on the liver surface after hepatectomy: an experimental swine study

Abstract: The present study aimed to determine the impact of different sealant materials on histopathological changes to the liver surface after liver resection. Thirty-six landrace pigs underwent left anatomical hemihepatectomy and were assigned to a histopathological control group (HPC, n = 9) with no bleeding control, a clinically simulated control group (CSC, n = 9) with no sealant but bipolar cauterization and oversewing of the liver surface, and two treatment groups (n = 9 each) with a collagen-based sealant (CBS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This is probably partly owing to the locally released copper ions by the COCu hydrogel, which promote vascular regeneration and tissue repair. [33,[43][44][45] Further, the rat liver regeneration ability and recovery were evaluated according to the expression levels of the proliferative nuclear antigen (PCNA), as measured by a quantitative reverse transcription -polymerase chain reaction (qRT-PCR) assay and Western blot (WB) for the different groups. In general, after liver tissue injury, the expression of PCNA first increases (within 24 h) and then decreases, leveling off at 72 h to 120 h. The level of PCNA thus can be used as an indicator of the liver recovery and regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably partly owing to the locally released copper ions by the COCu hydrogel, which promote vascular regeneration and tissue repair. [33,[43][44][45] Further, the rat liver regeneration ability and recovery were evaluated according to the expression levels of the proliferative nuclear antigen (PCNA), as measured by a quantitative reverse transcription -polymerase chain reaction (qRT-PCR) assay and Western blot (WB) for the different groups. In general, after liver tissue injury, the expression of PCNA first increases (within 24 h) and then decreases, leveling off at 72 h to 120 h. The level of PCNA thus can be used as an indicator of the liver recovery and regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in the dtCOCu group, there is barely any adhesion, with no hydrogel remaining on the incision surface, and the incision wound is healed with a flat and pale white new tissue (Figure 8a, 7d dtCOCu, yellow dotted line). In addition, the intra-abdominal adhesions were assessed for their qualitative aspects as in the previous literature, [43,44] and adhesion scores of each group are summarized in Table 1. The adhesion scores of COCu (1.8 ± 0.2) and dtCOCu (1.2 ± 0.2) are lower than those of the GG (2.6 ± 0.25) and CG (2.4 ± 0.25) groups, respectively, most likely owing to the anti-inflammatory and antibacterial properties of the copper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies (64%) reported enough available data to confirm the volume of resected lobes (Table 3), showing the different types of resections with different interpretations of the amount of RLV considered. [32] Mini LL, LM -Fonouni et al [36] Mini LL, LM, RM -Kohler et al [34] Mini LL, LM, RM 30 Inomata et al [42] Mini LL, LM, RL 40 Bekheit et al [37] Mini LL, LM, RM 25 Bucur et al [48] Large LL, LM, RM 25 Chen et al [43] Large LL, LM, RM, partial RL 15 Ge et al [39] Large --Orue-Echebarria et al [38] Mini LL, LM, RM, RL 10 Asencio et al [49] Mini LL, LM, RM, RL 10 Wittauer et al [35] Mini, Large LL, LM A direct hepatectomy was performed in 32 of 36 studies that considered PH (89%). Nine articles evaluated liver regeneration as a response to PVE, PVL, and ALPPS.…”
Section: Remnant Liver Volume (Rlv) and Surgical Proceduresmentioning
confidence: 97%
“…Among the ALPPS models, only Croome et al [55] performed an extended-left hepatectomy with a described RLV of 15-20%. The remaining three ALPPS authors [44,46,47] reported the type of resection (left hepatectomy) without quantification of RLV, and this also happened in 10 studies concerning direct hepatectomy [30,32,33,36,41,44,46,47,66,68]. Only two studies considered a hepatotoxic pre-treatment using retrorsine [42] or carbon tetrachloride (CCl4) and alcohol [56].…”
Section: Remnant Liver Volume (Rlv) and Surgical Proceduresmentioning
confidence: 99%